Legal Implementation of the Cancellation of Grants to Adoptive Children who Neglect the Grantor Based on the Civil Code - Kusumawati, Nita; Permadi, Iwan; Phra Harini, Novitasari Dian (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
In the case of the above decision, the judge granted the plaintiff's claim to cancel the grant deed and the grant object returned to the rights of the grantor. With the judge's consideration that the adopted child in this case the grantee has neglected the adoptive parents. However, there is a contradiction when referring to the Civil Code, the grantee as an adopted child is not an heir who is obliged to provide alimony obligations to his adoptive parents. This research uses normative legal methods, where law is conceptualized as what is written in legislation (law in books) and as rules or norms that become benchmarks of human behavior that are considered appropriate. This research is based on primary and secondary legal materials, focusing on the norms contained in the legislation. In brief, Grant according to the Civil Code is a free gift made by a person to another party while still alive. However, the obligation of alimony in the Civil Code only regulates biological children to parents, not including adopted children, resulting in a legal vacuum regarding the obligation of alimony of adopted children to adoptive parents. This causes legal uncertainty, even though there is a legal basis for canceling a grant if the recipient does not provide alimony to the grantor. This legal vacuum makes it difficult to apply the principle of grant cancellation in the context of adopted children.